Frailty and Risk of Cardiovascular Diseases in Older Persons: The Age, Gene/Environment Susceptibility-Reykjavik Study - Veronese, Nicola; Sigeirsdottir, Kristin; Eiriksdottir, Gudny; Marques, Elisa A; Chalhoub, Didier; Phillips, Caroline L; Launer, Lenore J; Maggi, Stefania; Gudnason, Vilmundur; Harris, Tamara B (Rejuvenation research, 2017)
Frailty is a risk factor for cardiovascular diseases (CVD), but the studies available have not considered the presence of subclinical atherosclerotic disease as potential confounders. We investigated the association between frailty and the onset of CVD independently of subclinical atherosclerotic disease. For this reason, a sample of 3818 older participants participating in the Age, Gene/Environment Susceptibility-Reykjavik Study without CVD at baseline was followed for a median of 8.7 years. Frailty was defined as the presence of ≥3 among five Fried's criteria (unintentional weight loss, low physical activity level, weakness, exhaustion, and slow gait speed). Incident CVD was defined as onset of coronary artery disease, heart failure, stroke, and CVD-related mortality identified using hospital, medical, and death records. Subclinical atherosclerotic disease was evaluated as the maximum value of carotid intima media thickness, presence of carotid plaque (moderate or high), and total coronary calcifications (CACs). At baseline, frail participants (n = 300) were more frequently obese, diabetic, and had a greater presence of metabolic syndrome than the nonfrail (n = 3518). Frail participants also showed a higher presence of carotid plaques and CACs. Using a Cox's regression analysis, adjusted for clinical, biochemical, and subclinical atherosclerosis estimates, frailty increased the risk of CVD (hazard ratio [HR] = 1.35; 95% confidence interval [CI]: 1.05-1.74), with results stronger for women than men (HR = 1.51, p = 0.006 and 1.19, p = 0.44, respectively). Among Fried's criteria, exhaustion was the only criterion significantly associated with the onset of new CVD events (HR = 1.30; 95% CI: 1.00-1.73). In conclusion, frailty was associated with the onset of CVD in older people even after adjusting for subclinical atherosclerotic disease.